Focusing on Gordonia Infections: Distribution, Antimicrobial Susceptibilities and Phylogeny - Silvia Pino-Rosa; María J. Medina-Pascual; Gema Carrasco; Noelia Garrido; Pilar Villalón; Mónica Valiente; Sylvia Valdezate (MDPI AG, 2023)
The immunosuppression conditions and the presence of medical devices in patients favor the Gordonia infections. However, the features of this aerobic actinomycete have been little explored. Strains (n = 164) were characterized with 16S rDNA and secA1 genes to define their phylogenetic relationships, and subjected to broth microdilution to profile the antimicrobial susceptibilities of Gordonia species that caused infections in Spain during the 2005-2021 period. Four out of the eleven identified species were responsible for 86.0% of the infections: Gordonia sputi (53.0%), Gordonia bronchialis (18.3%), Gordonia terrae (8.5%) and Gordonia otitidis (6.1%). Respiratory tract infections (61.6%) and bacteremia (21.9%) were the most common infections. The secA1 gene resolved the inconclusive identification, and two major clonal lineages were observed for G. sputi and G. bronchialis. Species showed a wide antimicrobial susceptibility profile. Cefoxitin resistance varies depending on the species, reaching 94.2% for G. sputi and 36.0% for G. terrae. What is noteworthy is the minocycline resistance in G. sputi (11.5%), the clarithromycin resistance in G. bronchialis secA1 lineage II (30.0%) and the amoxicillin-clavulanate and cefepime resistance in G. terrae (21.4% and 42.8%, respectively). G. sputi and G. bronchialis stand out as the prevalent species causing infections in Spain. Resistance against cefoxitin and other antimicrobials should be considered.